Investigation on the Growth and Properties of Six Garnet Single Crystals with Large Lattice Constants. Issue 5 (22nd March 2021) - Han, Zhiyuan; Sun, Dunlu; Zhang, Huili; Luo, Jianqiao; Quan, Cong; Hu, Lunzhen; Dong, Kunpeng; Cheng, Maojie; Chen, Guangzhu; Hang, Yin
Abstract: Large lattice constant Y3 Al5 O12, Gd3 Ga5 O12 (GGG), Y3 Sc2 Ga3 O12 (YSGG), Gd3 Sc2 Ga3 O12, Ca0.4 Mg0.25 Zr0.65 Gd2.6 Ga4.1 O12 (CaMgZr:GGG), and Gd1.17 Y1.83 Sc2 Ga3 O12 (GYSGG) substrate crystals with 2 in. in diameter are grown by the Czochralski (Cz) method, their physical, chemical, and optical properties are analyzed and compared in details. The X‐ray rocking curves (XRCs) illustrate that the as‐grown crystals possess high crystalline quality. The lattice constants of six crystals are calculated and that of GYSGG can be easily adjusted in the range of 1.2450–1.2565 nm by changing the Gd/Y proportion. The dislocation densities on the (111)‐crystalline face are about 10 2  cm −2 order of magnitude. The thermal conductivities of six crystals are measured to be 11.72, 8.98, 6.83, 5.45, 4.67, and 4.66 W m −1  K −1, respectively. It is found that the thermal expansion coefficients of six crystals can be reduced by annealing at 1273 K for 60 h. In addition, the transmission spectra show that the six crystals have excellent transparency and the coefficients of the Sellmeier equation are fitted by the calculated refractive indices. These results of the six crystals can provide the necessary parameters and references for the selection of suitable substrate materials or laser host crystals. Abstract : In this paper, the properties of six garnet crystals are compared in details. The annealing process can reduce the thermal expansion coefficients. The Gd1.17 Y1.83 Sc2 Ga3 O12 is an ideal substrate material with large and an adjustable lattice constant. These results can provide a useful reference for selecting suitable substrate materials or laser host crystals.